ANALISIS TINGKAT AKURASI GLOBAL POSITIONING SYSTEM SMARTPHONE DALAM MENENTUKAN TITIK LOKASI PADA GOOGLE MAP - Imanda Amalian Tafa . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2018)
Mobile devices offer sophisticated computing capabilities called Smartphones. There are many applications in it, one of the applications used to show the way, the address or position we are located through the Google Map application with the help of GPS Smartphones, Google Map can easily find the position we are located but the accuracy level is less precise target. Measurement of accuracy in this study was done by comparing the results obtained from Google Map with the results obtained at the actual distance in the field. Measurement by finding the big difference between two mobile operators namely Tri operator and Telkomsel operator and using two types of Smartphone that is Samsung Note 1 and Samsung J3. Tri cellular operators on the 3G network were found to have higher percentage errors compared to Telkomsel operators. This is indicated by obtaining a higher error percentage value of 1.997% (Tri) and 1.754% (Telkomsel) due to internet speed and stability of Google Map pada point location movement Telkomsel operators are better. While on 4G network obtained error value percentage of 1,495% (Tri) and 1.22% (Telkomsel). The result is that there is a decrease in both operators but Telkomsel operators still get better results. The selection of operators and the availability of networks greatly influence the determination of the accuracy level because it will affect the movement of points on the Google Map so that the difference in distance obtained is different. Keywords: GPS Smartphone, Google Map, Accuracy Level, Tri Operator, Telkomsel Operator.